На этот вопрос уже отвечает максимальное количество людей

Ответы и объяснения

  • Участник Знаний
2014-02-02T20:51:32+00:00
Лучший Ответ!
  • 1996sasha
  • почетный грамотей
2014-02-02T21:36:48+00:00
(Х-1)(х-2)(х-3)=3
(Х^2-3x+2)(x^2-3x)=3
Замена у=х^2-3х
(у+2)*у=3
у^2+2у-3=0
Д=16
у1=1. у2=-3
Х^2-3х-1=0
Д=13
х1=(3+V13)/2. X2=(3-V13)/2
Или х^2-3х+3=0
Корней нет D<0

---------------
(X+2)(x+3)(x+4)(x+5)=3
(X^2+7x+10)(x^2+7x+12)=3
y=x^2+7x. Замена
(У+10)(у+12)=3
У^2+10у+12у+120=3
У^2+22у+117=0
Д=16
У1=-13. у2=-9
Подставим
Х^2+7х+13=0
Д<0
Корней нет

Х^2+7х+9=0
Д=13
Х1=-7+V13)/2. X2=(-7-V13)/2